2006
DOI: 10.1007/s10750-006-0286-x
|View full text |Cite
|
Sign up to set email alerts
|

A multimetric index based on benthic macroinvertebrates for evaluation of Atlantic Forest streams at Rio de Janeiro State, Brazil

Abstract: This study describes the application of a protocol for biological assessment of water quality at first to third order streams at Serra dos Ó rgã os, an area covered by Atlantic Forest in Rio de Janeiro State, Brazil. Major impacts in the region are domestic effluents and deforestation. Our main objective is to establish biocriteria for the establishment of the Serra dos Ó rgã os Multimetric Index (SOMI) based on benthic macroinvertebrates. We used data from previous studies, sampled by experienced biologists, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
129
0
23

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(156 citation statements)
references
References 37 publications
4
129
0
23
Order By: Relevance
“…Many works demonstrate that benthic macroinvertebrates community can also be altered in response to anthropogenic environmental changes, as land uses (Miserendino et al 2011), riparian forest impacts and effluents loading (Baptista et al 2007, Couceiro et al 2007, Gamito & Furtado 2009, Sharma & Rawat 2009 and also by pollution by industrial effluents (Moreno & Callisto 2006). Several taxa from benthic macroinvertebrates community and a wide range of biological indexes and metrics have been widely employed as environmental indicators (Bode et al 2002, Mandaville 2002, Fusari & Fonseca-Gessner 2006, Baptista et al 2007, Baptista 2008, Angradi et al 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many works demonstrate that benthic macroinvertebrates community can also be altered in response to anthropogenic environmental changes, as land uses (Miserendino et al 2011), riparian forest impacts and effluents loading (Baptista et al 2007, Couceiro et al 2007, Gamito & Furtado 2009, Sharma & Rawat 2009 and also by pollution by industrial effluents (Moreno & Callisto 2006). Several taxa from benthic macroinvertebrates community and a wide range of biological indexes and metrics have been widely employed as environmental indicators (Bode et al 2002, Mandaville 2002, Fusari & Fonseca-Gessner 2006, Baptista et al 2007, Baptista 2008, Angradi et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Several taxa from benthic macroinvertebrates community and a wide range of biological indexes and metrics have been widely employed as environmental indicators (Bode et al 2002, Mandaville 2002, Fusari & Fonseca-Gessner 2006, Baptista et al 2007, Baptista 2008, Angradi et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…In an Atlantic Forest environmental quality assessment, Baptista et al (2007) concluded that shredder abundance was related to reference sites. In general, reference sites exhibit features that match with shredders demands, like litter accumulation and lower temperatures due riparian vegetation presence.…”
Section: Longitudinal Patterns In Shredders and Leavesmentioning
confidence: 99%
“…Based on the procedures described in Klemm et al (2003), Baptista et al (2007) and Baptista et al (2011) we followed four steps to develop the Multimetric Index for Serra da Bocaina (MISB). First we tested if metrics defined in the SOMI (Family Richness, Ephemeroptera + Plecoptera + Trichoptera (EPT) Richness, % Coleoptera, % Diptera, BMWP-CETEC, % Shredders) could be used for SB region.…”
Section: Development Of the Multimetric Index For Serra Da Bocaina (Mmentioning
confidence: 99%
“…Recently, there is a great effort to develop and test bioassessment protocols in Brazil using benthic macroinvertebrates (CETESB 2002;Baptista et al, 2007;Mugnai et al, 2008;Buss and Borges, 2008;Moreno et al, 2009, Buss and Vitorino, 2010Baptista et al, 2011;Ferreira et al, 2011, Couceiro et al, 2012. In Rio de Janeiro State, one multimetric index (Serra dos Órgãos Multimetric Index -SOMI; Baptista et al, 2007) was developed to Serra do Mar area. In this study, we developed and tested a Multimetric Index for Serra da Bocaina region (MISB), a different area in the same ecoregion.…”
Section: Introductionmentioning
confidence: 99%